PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, LOKASI DAN KENYAMANAN BERBELANJA, TERHADAP KEPUTUSAN PEMBELIAN DI PASAR TRADISIONAL JOHAR SEMARANG - Faishal Andry Laksana; Harries Arizona Ismail (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of service quality, price perception, location, and shopping comfort on purchasing decisions at Johar Traditional Market in Semarang. The research is based on the importance of traditional markets as centers of local economic activity, which are now facing challenges due to increasing competition from modern markets. The research method used is quantitative, employing a survey approach through questionnaires distributed to 100 respondents who are consumers of Johar Market. Data were analyzed using multiple linear regression with SPSS. The results indicate that all four independent variables service quality, price perception, location, and shopping comfort have a positive and significant effect on purchasing decisions, both partially and simultaneously. Among these, location is found to be the most dominant factor influencing purchasing decisions. These findings provide practical implications for market managers in designing strategies to enhance the appeal of traditional markets and strengthen consumer loyalty.